1990
DOI: 10.1148/radiology.174.1.2294541
|View full text |Cite
|
Sign up to set email alerts
|

Self-expandable stainless steel braided endoprosthesis for biliary strictures.

Abstract: A new type of biliary stent was inserted in 45 patients with symptomatic biliary strictures, 40 malignant and five benign. The stent is made of stainless steel woven into a tubular mesh. It is introduced in compressed form on a 7- or 9-F delivery catheter and released at the site of the stricture. Fully open, the stent has an internal diameter of 1 cm. The 30-day mortality was 7%. The early (less than 72 hours) complication rate was 16%. Recurrent jaundice occurred in 42%; late complications of sepsis without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
0
2

Year Published

1990
1990
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(54 citation statements)
references
References 0 publications
2
50
0
2
Order By: Relevance
“…Clinical trials have proven the superior effectiveness of the large internal diameter of these stents for bile drainage [1], compared with the smaller diameter of conventional plastic stents [2][3][4]. Metallic stents, however, provide efficient bile drainage for a defined period of time and then undergo obstruction which can be due to tumoral overgrowth and/or ingrowth, mucosal hyperplasia induced by chronic irritation caused by the stent mesh on the epithelium, biliary incrustation, sludge, and food impaction in transpapillary stents [5][6][7][8][9][10].In an earlier multicenter study in which various types of metallic endoprostheses were implanted in 240 patients with malignant biliary obstruction, we found that stents with a large space between struts favored early tumoral occlusion of the lumen [11]. In order to provide a complete obstacle to tumoral growth, selfexpandable stents covered with a thin polymeric compound were tested on animal models [12,13], and when good biological tolerability at 12 months was documented, covered stents were used in patients [14].…”
mentioning
confidence: 99%
“…Clinical trials have proven the superior effectiveness of the large internal diameter of these stents for bile drainage [1], compared with the smaller diameter of conventional plastic stents [2][3][4]. Metallic stents, however, provide efficient bile drainage for a defined period of time and then undergo obstruction which can be due to tumoral overgrowth and/or ingrowth, mucosal hyperplasia induced by chronic irritation caused by the stent mesh on the epithelium, biliary incrustation, sludge, and food impaction in transpapillary stents [5][6][7][8][9][10].In an earlier multicenter study in which various types of metallic endoprostheses were implanted in 240 patients with malignant biliary obstruction, we found that stents with a large space between struts favored early tumoral occlusion of the lumen [11]. In order to provide a complete obstacle to tumoral growth, selfexpandable stents covered with a thin polymeric compound were tested on animal models [12,13], and when good biological tolerability at 12 months was documented, covered stents were used in patients [14].…”
mentioning
confidence: 99%
“…Early results of percutaneous placement of both the Gianturco stent and the Wallstent were not encouraging and appeared not to be better than results with polyethylene stents [9, 17,28]. A 40-50% rate of recurrent jaundice and cholangitis was reported.…”
Section: Resultsmentioning
confidence: 99%
“…In a in larger patient population, furthermore, the question of whether they are related to the procedure or are due to other factors present in the patient population may be solved. Becker et al (18) and Gilliams et al (19) reported that in patients with hilar obstruction, the period of stent patency was shorter than in patients with non-hilar obstruction, but survival time was similar. However, after placing two stents (in a Y-configuration) in patients with hilar obstruction through both transhepatic tracts and then treating them with intraluminal brachytherapy, the mean duration of stent patency (8.3 months) was not different from that in all patients who underwent intraluminal brachytherapy.…”
Section: Discussionmentioning
confidence: 99%